Automated Intergrated System (AIS) Blueprint by Hyper Stark - Badrudin, Fathini; Mohamed Yusof, Mohamed Shafiq; Abu Bakar Ashe’ari, Nur Fadhlina; Wan Abdullah Zawawi, Wan Aida Nabila (2019)
Hyper Stark SDN BHD is an organization that is formed under a partnership that produces innovative washing machine which is Automated Integrated System (AIS). Our business main goal is to be one of the top company in Malaysia by providing our main product which is AIS that is unique. Our company also focuses on providing a good quality system to customer and give satisfaction to customer when using our product. Hyper Stark SDN BHn creates the AIS with some safety element to ensure that the user and the people near the washing machine are in protected from ant unwanted incident. The concept of our organization is to provide the best products that can help the laundry business more consistent and convenient.